Performance Obstacles and Workload of Nurses Working in Critical Care Unit at Teaching Hospital - Sunita Poudyal; Kalpana Sharma; Soni KC (Journal of Karnali Academy of Health Sciences, 2023)
Background: Performance obstacles are the elements of immediate workplace that restrict nurses' capacity to perform their duties. Performance obstacles are significant predictor of nurses' workload, which lowers their satisfaction and, in turn, affects their quality of work life. This study aimed to assess the performance obstacles and workload of nurses working in critical care unit.